Effect of Various Plant Extract Concentrations in Hair Tonic Preparations on Hair Growth Activity - Sari Dewi, Astika; Ridwan, Sucilawaty (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The prevalence of hair loss in Indonesia is quite high at 64.7%. One of the cosmetic products used by the public to overcome the problem of hair loss is hair tonic. Hair tonic with synthetic content such as minoxidil can cause side effects including skin allergies and edema, so an alternative from natural ingredients is needed. There are various kinds of plants that are formulated in the form of hair tonic preparations to stimulate hair growth. The purpose of this paper is to ascertain how test animal hair growth activity is affected by the concentration of different types of extracts that have been prepared as hair tonic preparations. In order to complete the writing process, a literature review is conducted by searching online journals from the Google Scholar platform using a variety of relevant keywords as well as from other scientific literature that has been published during the last ten years. The results of the literature review indicate that, for the majority of plants, the formula's highest concentration of plant extracts exhibits the best hair growth activity in test animals.